Nurturing Youth Character Education Through the “Sungkem Pertiwi” Cultural Performance - Sawitri; Pujiyana; Suyahman (CV Kalimasada Group, 2026)
Purpose – This study aims to analyze the influence of cultural arts performances on the character education of the younger generation. Design/Methodology/Approach – The research employs a qualitative approach, focusing on performances by various art groups, including karawitan, Javanese poetry (gurit jawa), Indonesian poetry, wayang padat (concise puppet shows), and dance. Data were gathered from primary and secondary sources through in-depth interviews, literature reviews, photographic documentation, and observations of digital content on platforms such as YouTube and TikTok. Findings – The results indicate that cultural arts performances have a positive and significant impact on character education. Through performance themes such as